Implementasi Aplikasi Bank Sampah Berbasis Web Sebagai Inovasi Pengelolaan Sampah Berkelanjutan. - Triyono Triyono; Hendri Hendri; Nur Ali Farabi; Nurul Afni; Rizky Ade Safitri (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
Waste management in densely populated areas remains a major challenge, particularly in terms of efficiency in recording and managing Waste Bank transaction data. The previous desktop-based system had limitations, such as being restricted to a single device, not supporting multi-user access, and lacking responsiveness to mobility needs. To address these issues, a web-based Waste Bank information system was developed, allowing access from various devices online. The aim of this development is to improve transaction management efficiency, simplify access for staff and customers, and provide flexible and accurate reporting features. The system supports real-time recording of waste deposit and withdrawal transactions, allows customers to monitor their balance and transaction history, and enables staff to work from multiple locations. With this web-based application, Waste Bank management is expected to become more modern, efficient, and inclusive.